Perspectiva etnoecológica do fogo na conservação de ecossistemas naturais - Rodrigues, Carolina Costa (2016)
The ecological importance of the region of Carrancas, Minas Gerais, Brazil, associated to the cultural aspect of the use of fire and to the occurrence of devastating wildfires in the ecosystems, reflects on the need for building strategies for environmental conservation and protection. In this context, we aimed at surveying knowledge and perceptions regarding controlled and rural fires recurrent in Carrancas; systematize the information obtained from municipal fire records; evaluate the forms of management of natural ecosystems; and correlate the perceptions observed and fire records with fire prevention, combat, monitoring and management strategies. The methodology was based on the principals of ethnoecology. We identified in the municipality, key social actors, indicated by experience of the research universe. Data collection was done by means of Focus Group, using participatory methodologies and semi-structured interviews. For data analysis, theme analysis, which is an instrument of content analysis, was used. From the audio transcriptions, it was possible to survey record units that, after grouping, generated two direction cores, subdivided into themes relevant to the analysis. 1) Historic perspective of fire, subdivided into: traditional fire management; exotic pasture management; impacts of field substitution and use of the ecosystem; rural fires; Lobo-Guará fire brigade; management and conservation of ecosystems; and 2) Fire ecological knowledge, subdivided into: relation between fire and flora; relation between fire and fauna; relation between fire, water resources and soil. The results were described according to the analyses of the core sense and theme subdivisions. The knowledge of fire management has been passed from generation to generation, consisting of intrinsic knowledge on ecologic fires. Two fire regimens were described, having occurred in March and September. However, the cultural changes in soil use has influenced the increase in the occurrence of fires in the last fifteen years. The different perceptions on fire are influenced by the experience of each group, location of origin and activities performed, showing the lack of involvement and participation of the different groups in managing the ecosystems. The knowledge surveyed from the fire regimens, of the areas susceptible to fires, and the information regarding the fires, must influence the planning of more effective strategies for fire prevention and management, and for the conservation of the ecosystems of Carrancas. It must also influence the formulation or reformulation of public policies based on local reality, which must be done in a participatory manner between the different social groups involved.